Peranan Muzium Nelayan Tanjung Balau, Kota Tinggi, Johor dalam mendokumentasi peradaban nelayan, 1994-2014 / Muhammad Khairul Latiff - Muhammad Khairul, Latiff (2016)
Museum is an institution that create awareness among the society throughout the collection that is being displayed. The foundation of Muzium Nelayan Tanjung Balau (Tanjung Balau Fishermen Museum) is important especially for the younger generation in its role conserving the fishermen’s culture. The main question in this research is to analyze the role of Muzium Nelayan Tanjung Balau, Kota Tinggi, Johor, in documenting the fishermen’s culture in Malaysia, especially in Tanjung Balau, Kota Tinggi, Johor. The objective of this research is to analyze the history of the founding of the Muzium Nelayan Tanjung Balau; to analyze the display in every gallery of the Muzium Tanjung Balau which includes the materials that is being kept for conservation and to review the activities that is being held by the museum. This analysis, which is focusing on the period of 20 years, beginning from 1994 until 2014, is to explore the history of the evolution and expanding exhibition at Muzium Nelayan Tanjung Balau, Kota Tinggi, Johor. The method of research is mainly library research by gathering primary and secondary sourcers. Apart from that, interview and observation were conducted to gain authentic info. The research is divided into 4 chapters. Chapter 1 deals with the history of early foundation of the museum; chapter 2 is on Main Gallery, chapter 3 is about other Galleries; chapter 4 is on Seasonal Gallery and the activity of the Museum and the final chapter is conclusion. Nowdays, the life and profession of fishermen are not well-known by others. With this type of research, it will help to conserve and provide useful information for future generation.